Reproductive biology of the rock oyster Striostrea prismatica in the southeastern Gulf of California - Zavala-Leal, Oscar Iram; Mena-Alcántar, Mariana; Valdez-González, Francisco; González- Huerta, Claudia Azucena; Cepeda-Morales, Jushiro; Pacheco-Vega, Juan Manuel; Cuevas-Rodríguez, Breidy (Ecosistemas y Recursos Agropecuarios, 2022)
The rock oyster Striostrea prismatica, is a natural resource of great commercial importance in the Mexican Pacific, Nayarit occupies the first place of production of oysters in this region. One of the main rock oyster extraction sites in Nayarit is Santa Cruz de Miramar, and according to the fishermen of the area, a decrease in the extraction volumes has recently been observed. The objective of this work was to describe the reproductive biology of the rock oyster and its relationship with temperature and chlorophyll-a. For this, 322 oysters were obtained from commercial fishing between January and December 2014. The organisms were weighed and measured individually. While the gonads were processed by histology. The sex ratio, condition index, reproductive cycle and size at onset of maturity were estimated. The surface water temperature and chlorophyll-a ranged from 25.5 to 30.6 °C and from 0.96 to 3.17 μg L−1, respectively. The sex ratio was 1M: 0.6 H (p < 0.05); the IC was higher from April to June, while the Ps/Ph proportion was higher from April to August. Spawning occurred between May to September. Temperature showed a direct association with maturity and spawning (p < 0.05). The size at first maturity was 80.2 mm. The results of this research could contribute to the management of the fishery of this resource in the  area.